Earplug usage routine with tinnitus and hearing loss among food processing factory workers - Dewi, Julita Melisa; Marliyawati, Dwi; Muyassaroh (BKM Public Health and Community Medicine, 2024)
Purpose: The earplug usage routine for workers exposed to noise serves as a preventive measure against the adverse effects of noise. Approximately 76.9% of earplug usage routines that are not adhered to during work are associated with tinnitus and hearing loss among workers. To know the correlation between earplug usage routine and the incidence of tinnitus and hearing loss among production workers. Methods: Analytical descriptive research with a cross-sectional design. A sample of workers exposed to noise in the production section of the food processing factory (92-110 dB) reported experiencing tinnitus and hearing loss. Tinnitus and earplug usage routines were assessed from the anamnesis, hearing loss was evaluated based on audiometry results, and noise level was measured using a sound-level meter. Data analysis was done using the chi-square test. Results: All samples consisted of 80 males, with an age range of 28 to 54 years (mean age 47.78±8.74 years). The duration of occupation was>10 years for 62 (77.5%) and <10 years for 18 (22.5%). Tinnitus was present in 48 samples (60%), hearing loss in 61 samples (76.25%), and routine earplug use in 51 samples (63.75%). Notably, earplug usage routines correlate with both the incidence of tinnitus (p < 0.000) and hearing loss (p < 0.000). Conclusion: The routine use of earplugs correlates with tinnitus and hearing loss in workers exposed to noise.